Effectiveness and Cost-Effectiveness of Different Weekly Frequencies of Pilates for Chronic Low Back Pain: Randomized Controlled Trial. Issue 3 (1st March 2016) - Miyamoto, Gisela Cristiane; Moura, Katherinne Ferro; Franco, Yuri Rafael dos Santos; de Oliveira, Naiane Teixeira Bastos; Amaral, Diego Diulgeroglo Vicco; Branco, Amanda Nery Castelo; da Silva, Maria Liliane; Lin, Christine; Cabral, Cristina Maria Nunes
Abstract : Background: The Pilates method has been recommended to patients with low back pain, but the evidence on effectiveness is inconclusive. In addition, there is still no evidence for the cost-effectiveness of this method or for the ideal number of sessions to achieve the highest effectiveness. Objective: The aim of this study will be to investigate the effectiveness and cost-effectiveness of the Pilates method with different weekly frequencies in the treatment of patients with nonspecific low back pain. Design: This is a randomized controlled trial with blinded assessor. Setting: This study will be conducted at a physical therapy clinic in São Paulo, Brazil. Participants: Two hundred ninety-six patients with nonspecific low back pain between the ages of 18 and 80 years will be assessed and randomly allocated to 4 groups (n=74 patients per group). Intervention: All groups will receive an educational booklet. The booklet group will not receive additional exercises. Pilates group 1 will follow a Pilates-based program once a week, Pilates group 2 will follow the same program twice a week, and Pilates group 3 will follow the same program 3 times a week. The intervention will last 6 weeks. Measurements: A blinded assessor will evaluate pain, quality-adjusted life-years, general and specific disability, kinesiophobia, pain catastrophizing, and global perceived effect 6 weeks, 6 months, and 12 months after randomization. Limitations: Therapists and patients will not be blinded. Conclusions: This will be the first study to investigate different weekly frequencies of treatment sessions for nonspecific low back pain. The results of this study will contribute to a better definition of treatment programs for this population.